2009
DOI: 10.1016/j.otc.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Septoplasty Pearls

Abstract: Techniques used for the diagnoses and treatment of septal deformity vary according to indications for the procedure and surgeon preference. Septoplasty is commonly performed to treat septal deformity causing nasal airway obstruction. Various preoperative and intraoperative "pearls" that the authors have found to be helpful in treating septal deformity and nasal airway obstruction are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Second, deviation of the septum differs between individuals and various types of deviation exist. For this reason, diverse techniques are required as the occasion demands [11,12]. Third, unlike endoscopic sinus surgery and rhinoplasty, few hands-on practice courses for septoplasty are held.…”
Section: Discussionmentioning
confidence: 99%
“…Second, deviation of the septum differs between individuals and various types of deviation exist. For this reason, diverse techniques are required as the occasion demands [11,12]. Third, unlike endoscopic sinus surgery and rhinoplasty, few hands-on practice courses for septoplasty are held.…”
Section: Discussionmentioning
confidence: 99%
“…For permission to copy go to https://www.oceansidepubl.com/permission.htm authors have noted the usefulness of external approaches to treat complex deviations. 32,33 Little further guidance as to the best approach for the severely deviated septum is offered in the literature, and no attempt has been made to assess results. An external septoplasty approach that maintains the septal L-strut has been described by Byrd et al Although they have used the approach primarily for cosmetic correction, they have not published functional outcomes for their cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be necessary to apply different techniques in different cases. [8,9] Heo et al [2] included six inexperienced surgeons in their study and analyzed the surgical results in the order of the operations performed. They reported that as surgical experience increased, surgical times became shorter and revision rates remained unchanged.…”
Section: Discussionmentioning
confidence: 99%